Commissions and Sales Targets Under Competition - Gallego, Guillermo; Talebian, Masoud (Management Science, 2014)
We consider a game between two capacity providers that compete for customers through a broker who earns commissions on sales and sells to both loyal and nonloyal customers. The providers compete by selecting commission margins and sales targets above which the margins on total sales increase. We study the contract form in equilibrium and the effect that sales targets have on the profit split between the providers and the broker. We show that in equilibrium, contracts require positive sales targets that can be best described as a mechanism for the larger provider to profit at the expense of the smaller provider. The effect of sales targets is different when commission margins are exogenous and the providers compete by setting targets. In this case, it is the low-margin provider who benefits from sales targets at the expense of the broker, who in this context resists the imposition of targets. This paper was accepted by Yossi Aviv, operations management.